Evaluating physician awareness of common health care costs in the emergency department. Issue 4 (29th June 2017) - Gandhi, Rohit; Stiell, Ian; Forster, Alan; Worthington, James; Ziss, Madeleine; Kitts, Jack B.; Malik, Ranjeeta
Abstract: Background: Health care costs are on the rise in Canada and the sustainability of our health care system is at risk. As gatekeepers to patient care, emergency department (ED) physicians have a direct impact on health care costs. We aimed to identify current levels of cost awareness among ED physicians. By understanding the current level of physician cost awareness, we hope to identify areas where cost education would provide the greatest benefit in reducing ordering costs. Methods: We conducted a survey evaluating current awareness of common ordering costs among ED physicians from two tertiary teaching hospitals. Our study population was comprised of 124, certified emergency medicine staff physicians and emergency medicine resident physicians. Our survey asked ED physicians to estimate the costs of 41 items across four categories of day-to-day ordering: imaging investigations, materials, laboratory tests, and pharmaceuticals. Items were selected based on frequency of use, availability of cost-effective alternatives, and tests considered to be "low yield". The primary outcome was percentages of underestimates, correct estimates, and overestimates for ED costs among ED physicians. Results: The average percentage of correct cost estimates among ED physicians was 14% across the four ordering categories. Where cost-effective alternatives exist, ED physicians overestimated the cost of the more cost-effective item. They also underestimated the cost of low-yield tests. Interpretation: ED physicians demonstrated limited cost awareness of common health care costs. Further studies that characterize utilization of hospital resources based on ED physician awareness of cost-effective alternatives and cost of "low yield" tests are needed. RÉSUMÉ: Contexte: Le coût des soins de santé augmente au Canada, ce qui compromet la pérennité du système de soins de santé. Les urgentologues, en tant que professionnels de première ligne, ont une incidence directe sur le coût des soins de santé. Aussi avons-nous tenté d'évaluer le degré de connaissance du coût de diverses demandes par les urgentologues. Ce faisant, nous espérons cerner les domaines où une formation en la matière se traduirait par les plus fortes réductions de coût. Méthode: Une enquête visant à évaluer le degré de connaissance du coût de demandes courantes par les urgentologues a été menée dans deux hôpitaux universitaires de soins tertiaires. La population à l'étude se composait de 124 urgentologues, membres du personnel, titulaires d'un certificat de compétences, et de résidents en médecine d'urgence. Les urgentologues devaient estimer, dans le questionnaire, le coût de 41 unités provenant de quatre catégories de demandes courantes, soit les examens par imagerie, le matériel, les examens de laboratoire et les médicaments. Le choix des unités reposait sur la fréquence d'utilisation, l'existence de solutions de rechange rentables et le faible degré de rendement de certains examens. Le principal critère d'évaluation consistait en les pourcentages de sous-évaluation, d'évaluation juste et de surévaluation du coût de certaines demandes faites par les urgentologues. Résultats: Le pourcentage moyen des évaluations justes du coût des unités a atteint 14 %, et ce, dans l'ensemble des quatre catégories. Dans les cas où il existait des solutions de rechange rentables, les urgentologues ont surestimé le coût des unités plus rentables. Ils ont toutefois sous-évalué le coût des examens jugés à faible rendement. Interprétation: Les urgentologues ont fait preuve d'une méconnaissance du coût des soins de santé courants. Il faudrait mener d'autres études qui caractérisent l'utilisation des ressources hospitalières, fondée sur la connaissance qu'ont les urgentologues des solutions de rechange rentables et du coût des examens à faible rendement.